Cognitive performances and subjective sleepiness among Croatian anesthesiology residents before and after 24-hour shift - Matas, M; Sekulic, A; Tadinac, M Hromatko, I; Ivancic, R (2010)
Cognitive performances and subjective sleepiness among Croatian anesthesiology residents before and after 24-hour shift M. Matas, A. Sekulic, M. Tadinac, I. Hromatko, R. Ivancic Department of Anaesthesiology and Intensive Care, University Hospital Zagreb, Zagreb, Croatia Background and Goal of Study: Fatigue, sleepiness and cognitive disorders caused workload limitations for USA anesthesia residents to 80 hours per week (1). Since 2003. these regulations are under debate considering the incidence of medical errors, the quality of education process and hospital costs (2). Aim of our study was to test the hypothesis that workload of 60 hours per week in anesthesia residents in Croatia still causes sleepiness and cognitive disorders after a 24 hour shift. Materials and Methods: A total of 26 anesthesiology residents (6 males, age range 26-35 yrs.) participated in the study. Inclusion criteria were: last two years of residency, less then 4 hours of sleep during the shift, and without any medication. Meal two hours prior to testing was not allowed. Room temperature was kept at 20 ° C during the testing. Caffeine intake was not controlled. The participants completed a set of psychological instruments in the morning at the begining and at the end of the 24 hours shift (Digit Span Test, Auditory Verbal Learning Test and Stanford sleepiness scale ). Testing lasted more then 30 minutes. Multivariate ANOVA was used for statistical analysis. Statistical significance was set at P = 0.05. Results and Discussion: There was a significant decline in cognitive performance measured by AVLT (a measure of immediate memory span) after the shift (F=3.19, p<.002). There were no differences in the Digits forward test (a measure of concentration), while Digits backward test (a measure of working memory) even showed an improved performance after the shift (F=4.74, p<.04 ). Participants reported being significantly sleepier after the shift (F=13.3, p<.001). Conclusion(s): Sleepiness and cognitive disorders after a 24 hour shift in anesthesia residents are still present even workload is reduced to 60 hours per week. References: 1 Accreditation Council for Graduate Medical Education. Report of the ACGME Work Group on Resident Duty Hours [Accreditation Council for GME web site], 2002. 2 Biller et al The 80-Hour Work Guidelines and Resident Survey Perceptions of Quality, Journal of Surgical Research 135, 275–281, 2006.
Projekt MZOS
Projekt MZOS
ENG